Credit guarantee institutions and SME finance - Leone, Paola; Vento, Gianfranco A., 1975- (Basingstoke : Palgrave Macmillan, 2012)
This book analyses and confronts the functioning of guarantee systems for SMEs in countries where these schemes had an important development. The book also highlights how the current financial crisis is modifying the guarantees schemes, through policy maker interventions.
Includes bibliographical references and index.
oif 09/09/14
Loan
Keywords: Credit -- Management; Small business -- Finance; Credit